2004
DOI: 10.1158/1535-7163.499.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous liposomal delivery of the snake venom disintegrin contortrostatin limits breast cancer progression

Abstract: Despite significant research in this area, metastatic breast cancer remains a disease with a poor prognosis. Until an effective therapy is developed, it is imperative that new treatment modalities be investigated. In this report, we describe an effective method for delivery of a novel snake venom disintegrin, contortrostatin (CN), in an orthotopic, xenograft model of human mammary cancer in immunodeficient mice. CN (Mr 13,500) is a homodimeric disintegrin isolated from venom of the Southern Copperhead snake. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(18 citation statements)
references
References 62 publications
1
14
0
3
Order By: Relevance
“…12 Unlike free RGD peptides, the disintegrin specificity and affinity is enhanced by the tertiary structure of the disulfide framework and the amino acid chain at the carboxy terminus of the disintegrin. 8,13−15 Although the pharmacological properties of the disintegrin CN have made it an intriguing molecule for potential anticancer therapeutic strategies, 16,17 it is produced in small quantities from snake venom (∼0.01%). To overcome this obstacle, a recombinant disintegrin was designed by the Markland laboratory, vicrostatin (VCN), which can be produced through heterologous expression in E. coli.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Unlike free RGD peptides, the disintegrin specificity and affinity is enhanced by the tertiary structure of the disulfide framework and the amino acid chain at the carboxy terminus of the disintegrin. 8,13−15 Although the pharmacological properties of the disintegrin CN have made it an intriguing molecule for potential anticancer therapeutic strategies, 16,17 it is produced in small quantities from snake venom (∼0.01%). To overcome this obstacle, a recombinant disintegrin was designed by the Markland laboratory, vicrostatin (VCN), which can be produced through heterologous expression in E. coli.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20−22 Previously Swenson et al determined the circulatory half-life of CN and liposomal CN, and it was observed that liposomal CN is cleared slowly compared to "naked" CN with a circulatory half-life of 19 and 0.5 h, respectively. 16 As an alternative to conventional macromolecular carriers, protein polymers are under investigation for transport and delivery of imaging and therapeutic agents. 23−25 These bioconjugates are typically large hydrophilic molecules linked to a therapeutic agent, which can target tumors either passively through enhanced permeability and retention or actively through affinity toward a molecular target.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The echistatin/contortrostatin chimera vicrostatin can be reliably produced recombinantly, avoiding difficulties in supplying contortrostatin in large quantities, 136 and contortrostatin itself has been produced recombinantly 137 and formulated as liposomes to improve half-life and facilitate intravenous administration. 138 Preclinical experiments with disintegrins indicate that multiantagonists of the RGD-binding integrins are effective, and generally safe, anticancer agents. Knowledge of disintegrin structures, specifically the conformation of the loop containing the recognition motif, and the nature of the amino acids flanking the RGD tripeptide will provide inspiration for small molecule development.…”
Section: ■ Anti-α V Antibodiesmentioning
confidence: 99%
“…Naturally produced supply is limited, expensive, and hazardous to collect, whereas recombinant disintegrins may have different properties compared to the naturally sourced material. The echistatin/contortrostatin chimera vicrostatin can be reliably produced recombinantly, avoiding difficulties in supplying contortrostatin in large quantities, and contortrostatin itself has been produced recombinantly and formulated as liposomes to improve half-life and facilitate intravenous administration …”
Section: Disintegrinsmentioning
confidence: 99%